Improvement of Pockels effect by crystallization-process control in nonlinear-optical glass-ceramics. Issue 13 (September 2019) - Otsuki, Tomoki; Takahashi, Yoshihiro; Terakado, Nobuaki; Fujiwara, Takumi
Abstract: We have fabricated perfectly-surface-crystallized glass-ceramics (PSC-GCs) consisting of polar frenoite-type Sr2 TiSi2 O8 by different crystallization-process conditions, i.e., isothermal treatment at 880 °C for 72 h and 960 °C for 1 h, and have examined their Pockels effect in this study. The PSC-GCs obtained by the lower-temperature process exhibited the Pockels coefficients, i.e., r 13 ∼ 3.0 pm/V and r 33 ∼ 2.4 pm/V, and the coefficients exceeded the reported values of the PSC-GCs with Sr2 TiSi2 O8 phase. The improvement of Pockels effect is attributed to the higher crystal-orientation, which is provided by the lower-temperature condition.